The degeneration of workers' cooperatives under endogenous membership in mixed oligopoly - Flavio Delbono; Carlo Reggiani (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2024)
We propose a new model of mixed oligopoly where a workers' cooperative firms competes with a number of profit maximising companies. Building upon a large empirical evidence, we innovate as compared to the traditional literature on the objective function of the cooperative; moreover, its membership is treated as endogenous in the Cournot-Nash equilibrium. We show which factors may be responsible of the degeneration of the workers' cooperative firms, which occurs when the number of members shrinks with respect to the overall employees.
Keywords: L21; L25; P13; 330; cooperatives; mixed oligopoly; degeneration